"Ex oriente..." Ten Composers from the Former USSR; "Ex oriente...II" - Fanning, David 1955- (Oxford University Press, Oxford, 2004)
RESUMEN: Autor Valeria Tsenova. Trans. by Romola Kohanovskaya. Studia Slavica Musicologica, 25, 30, 31. Ernst Kuhn, Berlin, 2002, 2003, 2003 ; Ernst Kuhn, Jascha Nemtsov and Andreas Wehrmeyer. Studia Slavica Musicologica, 32. Ernst Kuhn, Berlin, 2003